STRESS AND ACADEMIC ACHIEVEMENT IN RELATION TO DURATION OF SLEEP AND COURSE - Sarraf, Seema Rani; Dubey, S.N. (The Scientific Temper, 2017)
An average student gets 7 hours of sleep instead of the desirable 9.2 hours. This lack of sleep makes students less concentrated, and reduces their cognitive abilities. All this leads to decreased academic achievement. The study aimed to elucidate the effect of duration of sleep on stress and academic achievement in students studying professional and non-professional courses. A total of six hundred and eighty students, aged 20 to 25 years participated in this research. Purposive sampling technique was applied to select the subject. The groups formed on the basis of duration of sleep e.g. long sleepers (more than nine hours out of twenty- four hours) and short sleepers (less than six or fewer hours out of twenty- four hours). These are independent variables which were manipulated through selection. A self- biographical sheet and The Hassles Scale (Lazarus and Folkman, 1981)were used for the purpose of data collection. Student’s last three years academic performance was considered as their academic achievement. 2 x 2 Analysis of variance (ANOVA) was carried out to find out the significance of difference between the means of groups as well as interaction effects. A significant difference was found between long and short sleepers on stress variable. short sleepers were more stressful than long sleepers. Course opted by the students also differed on stress level. Professional group scored high on stress variable. A significant difference has been recorded for course variable. Professional group scored high on academic achievement variable. Duration of sleep had no significant effect on academic achievement.